Dialkyl‐fluoroquinoxaline–based polymeric donor for binary and ternary organic solar cell applications. Issue 7 (15th December 2022) - Agneeswari, Rajalingam; Ahn, Yoomi; Tamilavan, Vellaiappillai; Shin, Insoo; Shin, Chnan‐gi; Park, Sung Heum; Jin, Youngeup
Abstract: Here, we studied the potential of 2, 3‐didodecyl‐6‐fluoroquinoxaline–based polymer as an electron‐donor in binary and ternary organic solar cell (OSC) applications. A new wide bandgap polymeric donor, namely poly(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐ alt ‐2, 3‐didodecyl‐6‐fluoro‐5, 8‐di(thiophen‐2‐yl)quinoxaline) (P(BDTT‐TfQT)), is prepared. Polymer P(BDTT‐TfQT) showed intense absorption between 300 and 650 nm with an optical band gap of 1.83 eV. The determined highest occupied and lowest unoccupied molecular orbitals (highest occupied molecular orbital/lowest unoccupied molecular orbital = −5.28 eV/−3.45 eV) for P(BDTT‐TfQT) are found to be suitable to utilize as an electron donor along with widely used fullerene and non‐fullerene acceptors. The OSCs prepared by using P(BDTT‐TfQT):fullerene blend gave a maximum power conversion efficiency (PCE) of 4.64%, and the PCE further increased to 6.77% by using a non‐fullerene acceptor instead of fullerene. Overall, the improved light absorption results in higher photo‐current and PCE for P(BDTT‐TfQT):non‐fullerene blend compared to that of P(BDTT‐TfQT):fullerene blend. In contrast, the inclusion of 10 vol% of P(BDTT‐TfQT) as a third component in a high energy converting polymer: non‐fullerene blend is found to lower the performance from 16.03% to 14.50% for the resulting ternary OSCs. Abstract :